A Key to the Species of Spintharina With Descriptions of New Species and Indication of Species Groups (Hymenoptera, Chrysididae) - Richard M. Bohart (Psyche: A Journal of Entomology)
Spintharina Semenov (type species: vagans Radoszkowski occurs in the southern Palearctic and Ethiopian Regions. This group is characterized by the absence of teeth on tergum III, a long triangular forewing marginal cell, and an apically blunt or emarginate lateral propodeal projection. Fragmentary evidence points to Masaridae as hosts. have been able to study types or authentically determined specimens of 23 of the 26 species. Status of the other 3 is in doubt. Complete synonymy and distribution will be given in a generic revision of Chrysididae now in preparation by L. S. Kimsey and R. M. Bohart. I would like to thank Dr. Kimsey for turning over to me her basic research on the genus, and for reviewing this paper.